Pengaruh Faktor Sosial Ekonomi Terhadap Usia Kawin Pertama Wanita di Kecamatan Bangli - Kartika, Dwi; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 3, Maret 2016 (pp.316 - 384), 2016)
Uncontrolled population growth can lead to social problems in society such as poverty. One of the causes of the population growth is high birth rate, one of which was caused by decreasing age of first marriage. The research aims to determine the effect of education, work status and income on age at first marriage in the District Bangli. Data collected by observation, questionnaires and interviews unstructured. The sampling technique proportionate stratified random sampling with a sample of 99 respondents. The analysis technique used is multiple linear regression . The results showed that education, work status, and income simultaneously significant effect on age at first marriage of women in the District of Bangli . Then partially education, work status, and income positive and significant impact on the age at first marriage in the District Bangli.
Keywords: age at first marriage; fertility